2021
DOI: 10.1186/s40101-021-00256-y
|View full text |Cite
|
Sign up to set email alerts
|

Does change in barometric pressure per given time at high altitude influence symptoms of acute mountain sickness on Mount Fuji? A pilot study

Abstract: Background Acute mountain sickness (AMS) is a common, transient condition characterized primarily by headaches, and it can also be associated with fatigue, dizziness, and nausea with vomiting. The symptoms of AMS are most pronounced after the first night spent at a new altitude. At sea level, changes in barometric pressure per given time have been associated with migraine headaches. We sought to investigate whether changes in barometric pressure, subjective sleep quality index, and other candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Although high variance inflation factors (VIFs > 5) indicate multicollinearity [ 18 ], the VIFs were < 3 for all explanatory variables. To identify the optimal model containing the parameters to best explain the data, we performed model selection by backward stepwise elimination using Akaike Information Criterion based on our previous studies [ 19 , 20 ]. All statistical analyses were performed using R ver.…”
Section: Methodsmentioning
confidence: 99%
“…Although high variance inflation factors (VIFs > 5) indicate multicollinearity [ 18 ], the VIFs were < 3 for all explanatory variables. To identify the optimal model containing the parameters to best explain the data, we performed model selection by backward stepwise elimination using Akaike Information Criterion based on our previous studies [ 19 , 20 ]. All statistical analyses were performed using R ver.…”
Section: Methodsmentioning
confidence: 99%
“…Hasil penelitian ini tidak sesuai dengan penelitian yang dilakukan oleh Hou et al, (2019) yang menunjukkan bahwa terdapat hubungan antara jenis kelamin dengan risiko AMS dengan nilai p-value 0,000. Tetapi hasil penelitian ini sesuai dengan penelitian yang dilakukan oleh Horiuchi et al, (2021) yang menunjukkan bahwa tidak terdapat hubungan antara jenis kelamin dengan gejala AMS.…”
Section: Pembahasanunclassified
“…It has been reported that exposure to the high-altitude environment may trigger the overactivation of the sympathetic nervous system and the compensatory mechanism of the circulorespiratory system, this results in a series of physiological changes such as heart rat, blood pressure, and saturation of pulse oxygen that help acclimate the body to harsh environmental conditions [3,4]. However, when these physiological changes fail to occur, it results in a series of nonspeci c clinical symptoms, including headache, dizziness, fatigue, insomnia, anorexia, nausea, and vomiting [5]. More seriously, a small number of patients may develop life-threatening highaltitude pulmonary edema (HAPE) or high-altitude cerebral edema (HACE) under severe conditions and need emergency medical care [6][7][8].…”
Section: Introductionmentioning
confidence: 99%